2016
DOI: 10.3126/ajms.v7i5.15169
|View full text |Cite
|
Sign up to set email alerts
|

Hysterosalpingographic patterns and relevance in the management of infertility in a Nigerian tertiary health Institution

Abstract: Background: Infertility is a major clinico-social problem not only in Nigeria; but the whole of the sub-saharan Africa and other parts of the world. In Nigeria it accounts for over 50% of attendance in Gynaecological clinics. Hysterosalpingography (HSG) is still a very valuable imaging modality in the work-up of women with infertility; especially in some communities in Nigeria where modern non-invasive diagnostic modalities are not readily available in most of the health institutions.Aims and Objectives: The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
2
5
2
Order By: Relevance
“…These myomas were seen as impressions or filling defects when located in the sub mucous region. This is contrary to what was found by another study13 that reported uterine fibroids as the commonest anomaly, constituting 41.95% in 205 infertile women in Calabar. The difference may be due to diet (red meat and alcohol intake increases the risk of developing myomas14) and other cultural differences.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…These myomas were seen as impressions or filling defects when located in the sub mucous region. This is contrary to what was found by another study13 that reported uterine fibroids as the commonest anomaly, constituting 41.95% in 205 infertile women in Calabar. The difference may be due to diet (red meat and alcohol intake increases the risk of developing myomas14) and other cultural differences.…”
Section: Discussioncontrasting
confidence: 95%
“…The lower limit may be attributed to early marriages and lack of education noted in that period; while the upper limit may be due to assisted conception techniques that are now offered increasing the chances for perimenopausal women. Newer studies in the same population however had similar age ranges as this study 12,13. The mean age in this age group was also higher than that of the older studies but similar to those of the new studies likely because their upper limits were less than noted in the newer studies.…”
Section: Discussionsupporting
confidence: 73%
“…[29]. But this is contrary to a study done in Nigeria in 2016 where bilateral tubal occlusion was predominant over unilateral tubal occlusion [30]. The uterine fibroid was the second most common abnormalities found on HSG 57 (23.6%) similar to a study done in Sokoto Nigeria (25.5%).…”
Section: Indications Of Hysterosalpingographycontrasting
confidence: 62%
“…The uterine fibroid was the second most common abnormalities found on HSG 57 (23.6%) similar to a study done in Sokoto Nigeria (25.5%). Previous reports have shown that uterine fibroids were the main HSG finding 86 (41.9%) in a study done in a tertiary hospital in Nigeria [30]. Six (2.9%) participants presented with congenital malformation.…”
Section: Indications Of Hysterosalpingographymentioning
confidence: 81%
“…Our findings at the Cape Coast Teaching Hospital, Ghana, vary from those of Botwe et al from the Korle-Bu Teaching Hospital of Ghana, who found that 60.03% of their women had abnormalities on HSG [ 20 ]. Many other studies have reported much higher proportions: 98.19% in China [ 25 ], 92% in India [ 26 ], and 85.8% and 75% in Nigeria [ 11 , 27 ]. The possible explanation to the disparity in findings is likely due to exposure to infections such as sexually transmitted disease (STD) and pelvic inflammatory disease (PID).…”
Section: Discussionmentioning
confidence: 99%